Reconstruction of the Principle of Justice in the Islamic Inheritance Law System in Indonesia - Susi Aryani Manangin; Feibe Engeline Pijoh; Mujibur Rahman; Fatimah HS (CV. RADJA PUBLIKA, 2026)
This study aims to analyze the application of the principle of justice in the distribution of inheritance according to Islamic law in Indonesia, as regulated in the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI). The primary issue examined is how the principle of proportional justice manifests in the distribution of inheritance, as well as its practical implementation in the Religious Court (Peradilan Agama) in responding to the social dynamics of modern society. The research method employed is normative juridical with a conceptual approach. The findings reveal that justice in Islamic inheritance law does not always mean numerical equality (equal distribution), but is rather grounded in a balance between rights and obligations (the obligation of financial support/nafkah). However, in practice in Indonesia, there exists room for the application of substitute heirs (Ahli Waris Pengganti) and testamentary grants (Hibah Wasiat) as instruments to realize distributive justice for heirs who do not receive a portion under the faraid system. This article concludes that the principle of justice in Islamic law in Indonesia is dynamic, wherein legal certainty is maintained through the Quranic text, while substantive justice is achieved through judicial ijtihad and family agreement (takharuj).